Assessment of Tooth Preparation via Er:YAG Laser and Bur on Microleakage of Dentin Adhesives. - Zahra Bahrololoomi; Elham Heydari (Tehran University of Medical Sciences, 2014)
Microleakage can be responsible for tooth hypersensitivity, secondary caries, and the possibility of pathological pulp alterations in restored teeth. Recently, alternative methods for tooth preparation such as laser irradiation have been studied; but there are limited studies on primary teeth. The aim of this in vitro study was to compare the degree of microleakage of composite restorations prepared by Er:YAG laser and conventional bur preparation with two adhesive systems in primary teeth.Eighty primary canine teeth were randomly divided into 4 groups. Class V cavities were prepared by Er:YAG laser or diamond bur on buccal surface. The groups were as follows: group1: High speed drill + self-etching adhesive Adper Prompt-L-Pop, group 2: Er:YAG laser + etch & rinse adhesive Adper Single Bond, group 3: High speed drill + Adper Single Bond, group 4: Er:YAG laser + Adper Prompt-L-Pop. Cavities were restored with Filtek Z250 composite resin. Then all of the specimens were polished, thermocycled, immersed in 2% methylene blue solution and sectioned longitudinally. Degree of microleakage was evaluated by two evaluators who assigned the micrleakage score (0 to 3). The original data were analyzed by the Kruskal-Wallis and Dunn's tests.There were significant differences between bur-prepared cavities in the Adper Single Bond and other groups. There were no statistically significant differences between other groups.Laser-prepared cavities showed higher microleakage scores than cavities prepared with diamond bur with etch and rinse adhesive system. No significant difference was revealed between the laser and bur-prepared cavities using self-etch primers.